A shortage of funding or not enough healthcare projects? - Mike Eaton (Precision Nanomedicine)
The author, having worked in pharmaceuticals for several decades, has advised, in confidence, both investors and small to medium-sized enterprises on transitioning healthcare research projects into commercial development, mainly in Europe. He is now semi-retired. This note is written in the hope that his experience will improve the success of small and medium-sized enter-prises in their attempts to get non-academic investment funding and make life easier for investors. Whilst focused on drugs, the broader advice is relevant to other healthcare areas, such as diagnostics and devices.